Status indicators of formation of patriotic education of future teachers of physical culture - O.M. Onoprienko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to examine the formation of the system components of patriotic education of students. Material: the study involved 324 students of the first, third and fifth courses of National University. Results: the components of extracurricular activities and their relation with indicators of patriotic education are studied. Determined that the majority of students indicate the relevance and the need to implement the content of patriotic perspective, as well as patriotic educational activities. Determined that the implementation of the tasks of patriotic education is due to the specifics of the departments of the University. Focuses on the need to develop a system to introduce patriotic education in extracurricular activities. Conclusions: the training and educational system must have an integrated personality- developing character and to foster world students shape their patriotic outlook.